Cost‐effectiveness analysis of late prophylaxis vs. on‐demand treatment for severe haemophilia A in Italy. Issue 3 (8th February 2017) - Coppola, A.; D'Ausilio, A.; Aiello, A.; Amoresano, S.; Toumi, M.; Mathew, P.; Tagliaferri, A.; ,
Abstract : Introduction: Long‐term regular administrations of factor VIII (FVIII) concentrate (prophylaxis) initiated at an early age prevents bleeding in patients with severe haemophilia A (HA). The 5‐year prospective Italian POTTER study provided evidence of benefits in adolescents and adults of late prophylaxis (LP) vs. on‐demand therapy (OD) in reducing bleeding episodes and joint morbidity and improving quality of life; however, costs were increased. Aim: The aim of this study was to determine the cost‐effectiveness of LP vs. OD with sucrose‐formulated recombinant FVIII in adolescents and adults with severe HA in Italy. Methods: A Markov model evaluated lifetime cost‐effectiveness of LP vs. OD in patients with severe HA in Italy, from both the healthcare and societal perspectives. Clinical input parameters were taken from the POTTER study and published literature. Health utility values were assigned to each health state as measured by the joint disease severity Pettersson score. Costs were expressed in Euro (€) 2014, including drug and other medical costs. Sensitivity analyses were performed considering societal perspective (including productivity lost) and varying relative risk of bleeding episodes between regimens. Clinical outcomes and costs were discounted at 6% according to previous studies. Results: Lifetime incremental discounted quality‐adjusted life‐years (QALYs) were +4.26, whereas incremental discounted costs were +€229, 694 from a healthcare perspective, with estimated incremental cost‐effectiveness ratios (ICERs) equal to €53, 978/QALY. Sensitivity analyses confirmed the base‐case results showing lower ICERs with the societal perspective. Conclusion: Late prophylaxis vs. on‐demand therapy results in a cost‐effective approach with ICERs falling below the threshold considered acceptable in Italy.